Assessment of the Relationship between Alcohol Consumption and Food Addiction and Food Preferences in Young Adults - Cansu Bekar; Feray Gençer Bingöl; Sümeyye Kemaneci; Mustafa Özgür (Addicta: The Turkish Journal on Addictions)
Alcohol is a psychoactive substance that has addictive properties and affects health and nutrition. This study was conducted to evaluate the food preferences and food addictions of young adults according to their alcohol consumption status. In this study, sociodemographic characteristics, food addiction, alcohol, and food consumption frequency were assessed. Young adults were divided into 3 groups as non-consumers, 0–1 unit/day, and ≥1 unit/day alcohol consumers. The rate of smoking in participants who did not consume alcohol was lower than those who consumed 0–1 unit and ≥1 unit of alcohol (p < .001). The rate of physical activity in participants who consumed alcohol was higher than those who did not consume (p =.009). The mean body mass index of those who consumed ≥1 unit of alcohol was found to be higher than the other groups (p = .02). Daily average consumption of sunflower and pumpkin seeds, pastry products, popcorn, salty snacks, carbonated drinks, coffee, and energy drinks is positively correlated with the amount of alcohol consumption, while vegetables and fresh fruits are negatively correlated (p < .05). No statistically significant difference was found between the food addiction status of participants according to alcohol consumption. In conclusion, this study shows that alcohol consumption in young adults changes lifestyle habits as well as food preferences. It is very important to increase food and nutrition awareness in order to encourage healthy eating habits in participants who consume alcohol.